1990
DOI: 10.1079/bjn19900137
|View full text |Cite
|
Sign up to set email alerts
|

Lysine requirements and whole-body protein turnover in growing pigs

Abstract: The influence on protein accretion and whole-body protein turnover of changing dietary protein quality while maintaining constant energy intake was studied by varying the degree of lysine supplementation of a lysine-deficient barley-based diet given to growing pigs. Measurements of nitrogen metabolism and whole-body protein turnover, using both classical and 15N end-product methods following a single dose of [I5N]glycine, were made in 49-kg male pigs given diets containing 109 g lysine-deficient protein/kg sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
24
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
13
24
2
Order By: Relevance
“…The increase in whole-body N retention (or PR) achieved by supplementing lysine-deficient diets to reach requirements (NRC 1988) was a result of a greater increase in whole-body PS than in PD. This is in agreement with the findings of Salter et al (1990). In contrast, Fuller et al (1987a) observed that lysine supplementation increased net anabolism as a result of no significant increment of PS and of a numerical decrease in PD.…”
Section: Protein Metabolismsupporting
confidence: 75%
See 2 more Smart Citations
“…The increase in whole-body N retention (or PR) achieved by supplementing lysine-deficient diets to reach requirements (NRC 1988) was a result of a greater increase in whole-body PS than in PD. This is in agreement with the findings of Salter et al (1990). In contrast, Fuller et al (1987a) observed that lysine supplementation increased net anabolism as a result of no significant increment of PS and of a numerical decrease in PD.…”
Section: Protein Metabolismsupporting
confidence: 75%
“…Fuller et al (1987a) reported that the increase in protein retention (PR) observed with lysine supplementation of lysine-deficient diets appeared to be achieved through a numerical decrease in protein degradation (PD) without any change in PS. In contrast, Salter et al (1990) reported that the improvement of PR with lysine supplementation was due to the increase in PS exceeding that in PD. Despite an increase in protein retention, no major perturbations of whole-body energy metabolism were observed when lysine deficiency was corrected by dietary lysine supplementation (Noblet et al 1987;Fuller et al 1987b).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, excess lysine (diet 4) did not further increase growth or protein deposition rates, which emphasises the importance of the "ideal" protein in feeding of growing pigs. These results are consistent with the observation of Salter et al (1990). These authors stated that the addition of sufficient lysine to meet the requirements of growing pigs fed a diet containing barley and soyabean meal resulted in a significant increase in N retention and protein accretion, however, excess lysine did not increase protein deposition.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results have been demonstrated Nutrients for production and product quality in the growing pig (Salter et al, 1990) and in humans (Conway et al, 1980;Meredith et al, 1986). Studies performed using lysine-deficient diets have also revealed the possibility of a major effect of dietary amino acid levels on protein degradation: the fractional rates of proteolysis (values expressed as % per day) measured in the breast muscle of growing chickens are always higher in the lysine-deprived animals, irrespective of age or genotype (Tesseraud et al, 1996a and.…”
Section: Muscle and Adipose Tissue Metabolismsupporting
confidence: 87%